Mediatization and Hypermediation in Digital Religion and the Transformation of Indonesian Muslim Religious Practices through Social Media Usage - Sito Rohmawati, Hanung; Zulkifli; Hakiem, Nashrul (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
This article examines mediatization and hypermediation in digital religion concerning contemporary Muslim religious practices, particularly in Indonesia, through social media. This study employed a qualitative approach through library study of offline and online sources. The findings reveal that mediatization has altered the way Indonesian Muslims understand and practice their religion. Social media facilitates virtual religious practices and creates a hybrid space between online and offline religious activities. Hypermediation, through platforms such as Instagram and WhatsApp, strengthens individual religious identity and collectively reinforces religious communities. Social media also affects the structure of religious communities by challenging traditional authority through the emergence of popular religious figures in the virtual world. This article contributes significantly to understanding religious transformation in the digital age and is a foundation for further research. The article emphasizes the importance of understanding the social and cultural implications of integrating social media into Muslim religious practices in Indonesia. It highlights the complexity of the relationship between religion, technology, and identity in the current context of digital globalization